Hydration characteristics of tailing mud–42.5 OPC composite cementitious system and its application to dry-mixed mortar. (1st July 2023) - Duan, Dedan; Liao, Hongqiang; Wang, Jiana; Cheng, Fangqin
Abstract: This study investigated the influence of the raw material ratio on the product quality of tailing mud with type-I 42.5 ordinary Portland cement (OPC) in a binary cementitious system. In particular, this research aimed to expand the applicability of tailing mud and tailing waste rock while minimizing the production cost of dry-mixed mortar. The results demonstrated a synergistic reaction between the tailing mud and 42.5 OPC, which was beneficial for enhancing hydration and gelation, increasing the production of calcium silicate hydrate (C–S–H) and calcium hydroxide (C–H), promoting more free magnesium oxide (MgO) in the cement to participate in the hydration reaction, and improving the structure of the composite gelation system. When the concentration of tailing mud in 42.5 OPC was 20%, the cementitious block attained a 28-day compressive strength of 44.85 MPa. To manufacture the dry-mixed mortar product, 80% mud and 20% 42.5 OPC were mixed with equal amounts of tailing mud and waste rock aggregate. For the dry-mixed mortar, the 28-day compressive strength was 7.32 MPa, 2-h consistency-loss rate was 12.4%, and water retention rate was 99.2%. To further explore the synergistic reaction mechanism between the tailing mud and 42.5 OPC, the energy calculations, geometric optimization, and dynamic modeling of the tailing mud–42.5 OPC cementitious system were performed using the Forcite module in Materials Studio software. Overall, the results indicated that including tailing mud improved the mechanical strength of 42.5 OPC. Highlights: A tailing mud–42.5 OPC system with 20% tailing mud exhibits 28-day compressive strength greater than 44.85 MPa. The tailing mud promoted the hydration reaction of cement and enhanced the structure of the composite cementing system. Tailing mud–42.5 OPC mortar containing 80% mud satisfies the quality requirements of GB/T 25181-2010.